"Carefully and Cautiously": How Canadian Cultural Memory Workers Review Digital Materials for Private and Sensitive Information - Jess Whyte; Tessa Walsh (Partnership: The Canadian Journal of Library and Information Practice and Research, 2024)
This study is based on semi-structured interviews with digital preservation practitioners working in Canada. Participants included librarians, archivists, a library director, and technical systems staff. The goal was to understand how participants are reviewing for sensitive personal information in their digital materials, what they are doing with that information, and identify the challenges they face in this work. Qualitative research methods used leaned heavily on feminist methodologies (Stanley & Wise; Taylor) and the field of ethnography (Feldman, Bell & Berger; Emerson, Fretz & Shaw). Findings include a summary of current strategies in place (e.g., risk profiling, using software tools for triage, and consultation with donors and/or community), a list of challenges (e.g., IT or systems infrastructure, barriers to access for software tools, funding restrictions, and scale), and a series of recommendations (e.g., increasing staff resources, developing tools geared towards triage, and improving grant requirements to recognize this work).